RERATA WAKTU PELEPASAN TALI PUSAT BERDASARKAN JENIS PERAWATAN TALI PUSAT PADA BAYI BARU LAHIR DI KECAMATAN PATIKRAJA KABUPATEN BANYUMAS TAHUN 2009 - Zuniyati, Siti; Suryandari, Artathi Eka; Anasari, Tri (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2011)
The placenta treatment has purpose to prevent the neonatorum infection , because it is unsafe time for baby born. There are same indicators that in flounce the rest of placenta releasing. Beside by keeping the placenta dry and clean, it is also influenced by mother’s kasa to clean the placenta everyday. The Aim of the research is to identify the placenta treatment on baby born with the releasing time at Public Health Center of Patikraja. This research used the quasi experiment design with Time Series Design. The population of this research is baby born at Public Health Center of Patikraja on December 2009, they are 70 babies. The technique  of sampling is sampling quota, they are 60 babies. The description of the placenta treatment on baby are by using dry kasa are 20 babies, kasa of alcohol 70% are 20 babies, and kasa of povidone-iodine 10% are 20 babies. The average of the placenta releasing on baby brow at Public Health Center of  Patikraja by using dry kasa is 131 hours and 27 minutes, by using kasa of alcohol  70% is 174 hours and 43 minutes and by using kasa of povidone-iodine 10% is 138 hours and 25 minutes. The average of the placenta releasing on baby brow at Public Health Center of  Patikraja by using dry kasa is 131 hours and 27 minutes, by using kasa of alcohol  70% is 174 hours and 43 minutes and by using kasa of povidone- iodine 10% is 138 hours and 25 minutes.   Key words : the placenta treatment, the average of the placenta releasing.